Ultrasound-based structural health monitoring methodology employing active and passive techniques. (April 2023) - Etxaniz, Josu; Aranguren, Gerardo; Gil-García, José Miguel; Sánchez, Jesús; Vivas, Gabriel; González, Jon
Abstract: Currently, structures are examined during manufacturing by means of Non Destructive Tests (NDT), but there is an increasing interest in monitoring its integrity over its whole life cycle by using Structural Health Monitoring (SHM) strategies. The monitoring of aircraft structures is particularly important as they suffer high strain under extreme atmospheric conditions. There is an extensive literature on SHM for aviation available but there are few references on comprehensive methodologies. This article introduces a methodology, a device and the tests used in its validation. The electronic prototype for structural health monitoring applies ultrasound techniques by means of piezoelectric transducers. It is lightweight, has USB 2.0 connectivity and includes data pre-processing algorithms to improve its performance. It can run in pitch-catch and pulse-echo modes employing passive and active techniques. Passive techniques are used to detect impacts or fiber breakage in composite materials. Tests based on active techniques can bring to light several types of damages such as those caused abruptly or those produced progressively by corrosion, delamination or fatigue.